Bahasa nonverbal sebagai konteks dalam pembelajaran BIPA: kajian pragmatik edukasional - Pranowo Pranowo (Jurnal Bahasa Indonesia bagi Penutur Asing, 2019)
Non-verbal language learning as a context of Indonesian as foreign language learning needs serious attention because, in addition to learning verbal writing language, they also learn spoken language and cultural background. Therefore, learning must integrate an educationally linguistic approach with educational pragmatic words. Educational linguistic approaches in its nature are teaching the structure of language and its meaning, while a pragmatic approach or communicative approach is, in fact, the teaching of the use of languages and the context of its usage.  The problem in this article is "What is the role of non-verbal language as a context in Indonesian language learning for foreign speakers (BIPA), an educational pragmatic study?". The purpose of this study is (1) to describe the use of nonverbal language as a context that often accompanies verbal language, (2) want to set the BN learning that is related to verbal based on a pragmatic approach, (3) want to Describe the pragmatic nature of Educational, (4) want to describe the process of acquisition of BIPA integrated between verbal language with non-verbal language, (5) want to describe the role of BIPA teacher.